Pengaruh Etika Profesi, Pengalaman Auditor, Independensi dan Gaya Kepemimpinan Terhadap Kinerja Auditor BPKP Provinsi Sumatera Barat - Larasati; Wiwik Andriani; Rini Susanti (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to examine the influence of professional ethics, auditor experience, independence, and leadership style on auditor performance at the Badan Pengawasan Keuangan dan Pembangunan (BPKP) of West Sumatra Province. The research employed a quantitative method with a survey design, in which questionnaires were distributed to 90 BPKP auditors. Data were analyzed using multiple linear regression with the assistance of SPSS. The findings reveal that auditor experience, independence, and leadership style exert a positive and significant effect on auditor performance, whereas professional ethics does not show a significant effect. Furthermore, the independent variables collectively demonstrate a significant influence on the dependent variable.